Ultrafast light emission at telecom wavelengths from a wafer-scale monolayer graphene enabled by Fabry-Perot interferences - Lu, Kunze (2022)
Ultrafast light emission from monolayer graphene shows attractive potential for developing integrated light sources for next-generation graphene-based electronic-photonic integrated circuits. In particular, graphene light sources operating at the telecom wavelengths are highly desired for the implementation of graphene-based ultrahigh-speed optical communication. Currently, most of the studies on ultrafast light emission from graphene have been performed in the visible spectrum, while studies on ultrafast emission at the telecom wavelengths remain scarce. Here, we present experimental observations of strong ultrafast thermal emission at telecom wavelengths from wafer-scale monolayer graphene. Our results show that the emission spectra can be strongly modified by the presence of the cavity effect to produce an enhanced emission at telecom wavelengths. We corroborate our experimental results with simulations and show that by designing a suitable cavity thickness, one can easily tune the emission profile from visible to telecom wavelength regardless of the pump power. In addition, we demonstrate that the insertion of a monolayer of hexagonal boron nitride between graphene and the substrate helps improve the thermal stability of graphene, thereby providing more than five times enhancement of the ultrafast thermal emission. Our results provide a potential solution for stable on-chip nanoscale light sources with ultrahigh speed modulation.